2023
DOI: 10.32604/csse.2023.037055
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac CT Image Segmentation for Deep Learning–Based Coronary Calcium Detection Using K-Means Clustering and Grabcut Algorithm

Abstract: Specific medical data has limitations in that there are not many numbers and it is not standardized. to solve these limitations, it is necessary to study how to efficiently process these limited amounts of data. In this paper, deep learning methods for automatically determining cardiovascular diseases are described, and an effective preprocessing method for CT images that can be applied to improve the performance of deep learning was conducted. The cardiac CT images include several parts of the body such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Extrapolation using linear regression is a widely used method in numerous research fields for predicting data outside the observed range. In recent years, several studies have focused on developing advanced analysis models to enhance the accuracy of data prediction. The performance of the SoW is comparable to that of conventional measurement equipment obtained in another study, which measured blood flow using a Doppler wire in the coronary artery of experimental animals with the same type and similar weight and recorded a speed of 65–117 cm/s in the left main coronary artery.…”
Section: Resultsmentioning
confidence: 99%
“…Extrapolation using linear regression is a widely used method in numerous research fields for predicting data outside the observed range. In recent years, several studies have focused on developing advanced analysis models to enhance the accuracy of data prediction. The performance of the SoW is comparable to that of conventional measurement equipment obtained in another study, which measured blood flow using a Doppler wire in the coronary artery of experimental animals with the same type and similar weight and recorded a speed of 65–117 cm/s in the left main coronary artery.…”
Section: Resultsmentioning
confidence: 99%
“…The revised encoder in the form of U-Net encoder is utilized for segmentation and experimental study is performed on datasets like ARIA [38]. The authors employed grabcut technique with K-means clustering for enhancing the segmentation of CT scan images for various parts and deep learning techniques were used for detection of disease [39]. Authors suggested performing global average pooling, replacing the fully connected layer of the neural network to improvise the feature selection process, hence the image pre-processing procedure can be improved [40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Watershed-based segmentation methods are sensitive to noise and can lead to over-segmentation [5]. The GrabCut algorithm is an interactive segmentation technique that requires users to draw a rectangular bounding box on the image to indicate approximate regions of foreground and background [6]. The algorithm iteratively refines the segmentation results based on these markings.…”
Section: Introductionmentioning
confidence: 99%